The effectiveness of an intervention using LAWE (loveliness and well-being of employees) app to improve the employee’s mental well-being - Mohammad Ali Morowatisharifabad; Abedin Iranpour; Mohammadreza Rajabalipour (Health Promotion Perspectives, 2024)
Background: Organizations are increasingly seeking comprehensive approaches to improve employee mental well-being (EMW). This study aims to evaluate the effectiveness of interventions delivered through the "Loveliness and Well-being of Employees" (LAWE) app, focusing on five key predictors: "Keep Learning," "Connect," "Take Notice," "Be Active," and "Given". Methods: A quasi-experimental intervention was conducted with 110 participants (53 in the intervention group and 57 in the non-intervention group) from the Kerman University of Medical Sciences in Southeastern Iran. Participants were recruited from a census of all employees at four schools. The intervention involved an Android-based app designed to enhance EMW through pre-designed tasks. Six standard tools were used to assess EMW and its predictors. Data analysis was performed using IBM SPSS Statistics 28, employing Independent Samples T-Test, paired-samples t-test, one-way ANOVA, Spearman correlation coefficient and analysis of covariance (ANCOVA). Results: The intervention group showed a significant increase in mean EMW score, from 52.26±8.61 to 60.01±6.95 (P<0.01). Based on ANCOVA analysis, the post-intervention mean score was significantly higher in the intervention group compared to the non-intervention group by 0.219 points (P<0.01). The mean score of all predictors, except "Take Notice" (P=0.17), also significantly improved in the intervention group. Additionally, post-intervention comparison between the two groups revealed significant differences in mean EMW score (P<0.01), as well as in the mean scores for "Keep Learning" (P<0.05), "Given" (P<0.01), and "Connect" (P<0.01). Conclusion: The LAWE app provides a desirable and comprehensive platform for improving the EMW in organizations. It significantly improves most of the key predictors of EMW, making it a valuable resource for organizations aiming to promote employee well-being.